2021
DOI: 10.3389/fpls.2021.658755
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of GhACX3 Gene Reveals Its Significant Role in Enhancing Drought and Salt Stress Tolerance in Cotton

Abstract: The acyl-coenzyme A oxidase 3 (ACX3) gene involved in the β-oxidation pathway plays a critical role in plant growth and development as well as stress response. Earlier on, studies focused primarily on the role of β-oxidation limited to fatty acid breakdown. However, ACX3 peroxisomal β-oxidation pathways result in a downstream cascade of events that act as a transduction of biochemical and physiological responses to stress. A role that is yet to be studied extensively. In this study, we identified 20, 18, 22, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Protein CAT (A0A2G2YAF1 in Table S1) and peroxidase (POD) protein (A0A1U8EYL5 in Table S1) were up‐regulated upon exposure to MoS 2 NPs, consistent with the increase of CAT activity and peroxisome in Figure 3b, e. Fatty acid β‐oxidation initiates stress signaling in plants, with acyl‐coenzyme A oxidase (ACX) playing a role in the initiation step of the β‐oxidation pathway (Shiraku et al, 2021). The up‐regulation of ACX (A0A1U8EF39 in Table S1) with MoS 2 NPs exposure highlights its role in response to abiotic stress.…”
Section: Resultsmentioning
confidence: 64%
“…Protein CAT (A0A2G2YAF1 in Table S1) and peroxidase (POD) protein (A0A1U8EYL5 in Table S1) were up‐regulated upon exposure to MoS 2 NPs, consistent with the increase of CAT activity and peroxisome in Figure 3b, e. Fatty acid β‐oxidation initiates stress signaling in plants, with acyl‐coenzyme A oxidase (ACX) playing a role in the initiation step of the β‐oxidation pathway (Shiraku et al, 2021). The up‐regulation of ACX (A0A1U8EF39 in Table S1) with MoS 2 NPs exposure highlights its role in response to abiotic stress.…”
Section: Resultsmentioning
confidence: 64%
“…One such protein that was significantly decreased in abundance only in plants subjected to severe drought stress was putative acyl-CoA dehydrogenase (Q6ZDX3). Increasing acyl-CoA dehydrogenase accumulation under stress treatment has been reported to be a molecular response of plants which enables them to grow more rapidly [ 18 ], so decreasing the protein abundance under severe drought reflects the negative impact on plant growth of severe drought conditions. Except for growth, all six other biological functions responded to severe drought stress level by both increasing and decreasing the abundance of related proteins ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…There are conflicting reports about the role of β‐oxidation in osmotic stress responses. A recent report showed that the acyl‐coenzyme A oxidase 3 ( ACX3 ) gene, which is involved in the β‐oxidation pathway, plays a critical role in the stress response (Shiraku et al, 2021). Under osmotic stress, during which photosynthesis cannot provide energy, stored sugar can provide energy via glycolysis in the cytosol and the TCA cycle in mitochondria.…”
Section: Discussionmentioning
confidence: 99%